Unveiling the Experiences of Young ESL Educators in an Open Admission Academe - Aperocho, Maico Demi B.; Payot, Jennifer S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Many people consider teaching a noble profession. Teachers enter the education profession and are attracted to teaching as a career because of what they view as the role of the teacher. Also, teachers find their professions very rewarding. However, educators, specifically those who are new in the profession, encounter challenges too. This study seeks to understand the lived experiences of young college teachers handling English as a Second Language (ESL) courses in an open admission academe. In this study, a qualitative-phenomenological inquiry is employed. Seven young faculty members aged 20-25 years old with less than five years of teaching experience share their rewarding experiences, challenges, and hopes with ESL education in open admission academe. Triangulation is used in this study through three data-gathering and verification modes: in-depth interview, focus group discussion, and checklist. The experiences of the participants show that they have love for the profession, that they see teaching as a rewarding profession, and that disconnect still exists between teaching and their prior training. The participants also shared their stories on student learning and their experiences with the preparation programs and some practical elements in teaching. Participants also expressed that they too experience burdensome workload, stress, and burnout. It has been concluded that these faculty participants view their teaching career as fulfilling, challenging, and life-changing.